2015
DOI: 10.1088/2043-6262/6/2/025004
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization and adsorption ability of UiO-66-NH 2

Abstract: In this study UiO-66 and UiO-66-NH 2 were synthesized by solvothermal method. The effect of preparation conditions on the quality of UiO-66-NH 2 was studied. The obtained material has been characterized by x-ray diffraction (XRD), infrared spectroscopy (IR), thermogravimatric analysis (TGA), scanning electron microscopy (SEM) and nitrogen physisorption measurements (BET). The CO 2 and CH 4 physisorption measurements were carried out using a high pressure volumetric analyzer (Micromeritics HPVA-100). The result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
64
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 110 publications
(87 citation statements)
references
References 19 publications
20
64
1
2
Order By: Relevance
“…And finally, the third main step of weight loss was about 27% beyond 400 °C due to the decomposition of catalyst sample. As a result, the thermal stability of UiO66-NH 2 in this work was around 400 °C that was agreed with the result of other reports [15,17,21].…”
Section: Physicochemical Characteristics Of Materialssupporting
confidence: 93%
See 1 more Smart Citation
“…And finally, the third main step of weight loss was about 27% beyond 400 °C due to the decomposition of catalyst sample. As a result, the thermal stability of UiO66-NH 2 in this work was around 400 °C that was agreed with the result of other reports [15,17,21].…”
Section: Physicochemical Characteristics Of Materialssupporting
confidence: 93%
“…Amoni-functionalized UiO66 (UiO66-NH 2 ) was synthesized by a solve-thermal method, described in detail in our previous article [15], with a difference CH 3 OH was used as an exchanged solvent instead of CH 2 Cl 2 .…”
Section: Catalyst Synthesismentioning
confidence: 99%
“…The BET surface area and the total pore volume of UiO-66-NH 2 are 1384.6 m 2 g −1 and 0.654 cm 3 g −1 , respectively, much higher than UiO-66-NH 2 /TiO 2 , which are 671.7 m 2 g −1 and 0.0672 cm 3 g −1 , respectively. 30,31 The presence of TiO 2 in the UiO-66-NH 2 /TiO 2 nanocomposites is confirmed by the presence of the stretching vibration absorption peak arising from O-Ti-O at 562.6 cm −1 , while the other peaks of UiO-66-NH 2 remain unchanged. Fig.…”
Section: Resultsmentioning
confidence: 91%
“…On the P25, there is no inhibition of CO 2 because the rate of its production in the p ‐xylene photooxidation is low ( k is small), while on LaFeO 3 the suppression by CO 2 is strongest due to the highest value of reaction rate constant ( k ). The previous investigation showed that although adsorption capacity of UiO‐66 is not high compared to other MOFs, by adding functional groups in structures led to its increase in adsorption capacity. The experiments indicated that in comparison with UiO‐66 the addition of NH 2 could increase the CO 2 storage capacity at 1 bar and 303 K twice from 28.43 up to 52 cm 3 ⋅g −1 …”
Section: Resultsmentioning
confidence: 96%
“…The previous investigation showed that although adsorption capacity of UiO‐66 is not high compared to other MOFs, by adding functional groups in structures led to its increase in adsorption capacity. The experiments indicated that in comparison with UiO‐66 the addition of NH 2 could increase the CO 2 storage capacity at 1 bar and 303 K twice from 28.43 up to 52 cm 3 ⋅g −1 …”
Section: Resultsmentioning
confidence: 96%